2015
DOI: 10.1186/s12990-015-0047-9
|View full text |Cite
|
Sign up to set email alerts
|

Identification of IncRNA Expression Profile in the Spinal Cord of Mice following Spinal Nerve Ligation-Induced Neuropathic Pain

Abstract: BackgroundNeuropathic pain that caused by lesion or dysfunction of the nervous system is associated with gene expression changes in the sensory pathway. Long noncoding RNAs (lncRNAs) have been reported to be able to regulate gene expression. Identifying lncRNA expression patterns in the spinal cord under normal and neuropathic pain conditions is essential for understanding the genetic mechanisms behind the pathogenesis of neuropathic pain.ResultsSpinal nerve ligation (SNL) induced rapid and persistent pain hyp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
74
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 76 publications
(78 citation statements)
references
References 60 publications
4
74
0
Order By: Relevance
“…The data described here shows that SNI induces a very clear difference in the mouse DRG 7 days after surgery between the marked 50-fold increase in Gpr151 mRNA and the modest, though significant, 20% decrease in the related receptors GalR1 and GalR2. These changes are comparable to previous reports: Reinhold described a 14.1 fold increase in Gpr151 in mouse DRG 7 days after the chronic constriction model of neuropathic pain (Reinhold et al, 2015) whilst Jiang described a 27.7 fold change in mouse DRG 10 days after the spared nerve ligation model of neuropathic pain (Jiang et al, 2015). The changes in DRG GalR1 and GalR2 mRNA expression are also comparable to previous reports following complete section of the sciatic nerve (axotomy), using in situ hybridization (Sten Shi et al, 1997, Xu et al, 1996) and quantitative RT-PCR (Hobson et al, 2006).…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…The data described here shows that SNI induces a very clear difference in the mouse DRG 7 days after surgery between the marked 50-fold increase in Gpr151 mRNA and the modest, though significant, 20% decrease in the related receptors GalR1 and GalR2. These changes are comparable to previous reports: Reinhold described a 14.1 fold increase in Gpr151 in mouse DRG 7 days after the chronic constriction model of neuropathic pain (Reinhold et al, 2015) whilst Jiang described a 27.7 fold change in mouse DRG 10 days after the spared nerve ligation model of neuropathic pain (Jiang et al, 2015). The changes in DRG GalR1 and GalR2 mRNA expression are also comparable to previous reports following complete section of the sciatic nerve (axotomy), using in situ hybridization (Sten Shi et al, 1997, Xu et al, 1996) and quantitative RT-PCR (Hobson et al, 2006).…”
Section: Discussionsupporting
confidence: 90%
“…Several groups have used a range of techniques, which include transcriptional profiling and real-time quantitative RT-PCR, to identify and then quantify changes in gene expression in the rodent DRG and/or dorsal horn of the spinal cord after nerve injury models of neuropathic pain (Costigan et al, 2002, Griffin et al, 2003, Jiang et al, 2015, Reinhold et al, 2015). The data described here shows that SNI induces a very clear difference in the mouse DRG 7 days after surgery between the marked 50-fold increase in Gpr151 mRNA and the modest, though significant, 20% decrease in the related receptors GalR1 and GalR2.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies have also shown that peripheral noxious stimuli induced changes in the expression of lncRNAs, which are associated with pain hypersensitivity underlying NP (Zhao et al, 2013). Previous research studies performed gene chip studies to screen and predict DE lncRNAs in the spinal cord SNL model mice (Jiang et al, 2015). Although much evidence has been found, no comprehensive analysis on ncRNAs involved in NP has been performed.…”
Section: Discussionmentioning
confidence: 99%
“…LncRNAs have served as important molecules which can regulate gene expression at transcriptional and post‐transcriptional levels (Knauss & Sun, ). It has been reported that identifying abnormal lncRNAs in the spinal cord under neuropathic pain conditions helps to understand the genetic mechanisms of neuropathic pain (Jiang, Sun, & He, ). For example, a kind of lncRNA can contribute to neuropathic pain by inhibiting Kcna2 in primary afferent neurons (Zhao, Tang, & Zhang, ).…”
Section: Introductionmentioning
confidence: 99%